APLIKASI PENJUALAN TIKET DI TRAVEL JAYA SAKTI SURAKARTA - Kumalasari, Dewi; Retnoningsih, Dwi; Susilo, Dahlan (JURNAL GAUNG INFORMATIKA, 2014)
Ticket Service in Travel Jaya Sakti Surakarta currently still using manual processing system. Passenger data search, car data, a data driver and delivery of goods not used exclusive for data processing applications. However this method has some drawbacks, especially often occurs errors and takes a long time in recording and search the data. The purpose of this study is to develop data processing system and existing information on Travel Jaya Sakti. Systems development using a structured method. Products resulting from this research is a Information System Ticket Service In Jaya Sakti Travel Surakarta. After testing by the method of McCall, this system get the value of total quality 75,907%. Therefore the results of these test, This system is expected to facilitate the processing data and presenting information so that it can be applied in Travel Jaya Sakti.